Cationic gold(I) axially chiral biaryl bisphosphine complex-catalyzed atropselective synthesis of heterobiaryls - Shibuya, Tetsuro (Beilstein-Institut, 2011)
It has been established that a cationic gold(I)/(R)-DTBM-Segphos or (R)-BINAP complex catalyzes the atropselective intramolecular hydroarylation of alkynes leading to enantioenriched axially chiral 4-aryl-2-quinolinones and 4-arylcoumarins with up to 61% ee.